Strategy management for community empowerment in the Ekang Anculai tourism village - Kurnianingsih, Fitri; Muliawaty, Lia (Indonesian Tourism Journal, 2024)
The tourist village is a regional development concept that makes the village a tourist destination. Proper management of all tourist attractions is expected to empower the village community. However, in Bintan Regency, in developing tourism by empowering village communities that show good quality, one of them is Ekang Tourism in Ekang Anculai Village. This study aimed to identify management strategies for managing Ekang Tourism in Ekang Anculai Village by looking at environmental factors, formulation, implementation, evaluation, and control using Wheelen and Hunger's theory (2012). The research method uses a qualitative method by using secondary data and some informant data that researchers can get from the field and then analyze in depth. Data analysis techniques were carried out using triangulation techniques relevant to research case studies following the phenomena in the factual evidence that occurred. The study results show that in analyzing management strategies for managing Ekang tourism in Ekang Anculai Village there is an ongoing collaboration process on Wheelen and Hunger's theory (2012). In addition, researchers also found that community empowerment was carried out in the early stages until now, so the tourism concept was built to take advantage of the potential of Natural Resources and Human Resources in Ekang Anculai Village. But strategic management innovation must be implemented to develop a sustainable strategic management concept. This means that this alternative is needed to anticipate some small mistakes and can be corrected as quickly as possible in future strategic innovations in the management of Ekang tourism in Ekang Anculai Village.